2022
DOI: 10.1098/rsos.220014
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free decarboxylation of 4-hydroxycinnamic acids: efficient synthesis of 4-vinylphenols

Abstract: We report herein an efficient protocol for the synthesis of 4-vinylphenols by a catalyst-free decarboxylation of trans -4-hydroxycinnamic acids. A variety of 4-vinylphenols has been synthesized in moderate to excellent yields. This protocol also features no polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In a more recent investigation, it was reported that heat treatment in polar and protic solvents enabling proton transfer resulted in a yield twice as high compared to reactions performed in apolar media. In contrast to the data discussed herein, longer reaction times (30 min at 200 °C) were needed for a comparable conversion of caffeic acid, and no polymerization of 4-vinylcatechol was reported under these conditions [ 13 ]. In the present study, a revised mechanism that does not require any medium for proton transfer and makes the rapid conversion of caffeic acid more plausible is proposed in Figure 4 : Under roasting conditions, caffeic acid 1 performs an intramolecular proton transfer and decarboxylation, yielding 4-vinylcatechol 2 .…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…In a more recent investigation, it was reported that heat treatment in polar and protic solvents enabling proton transfer resulted in a yield twice as high compared to reactions performed in apolar media. In contrast to the data discussed herein, longer reaction times (30 min at 200 °C) were needed for a comparable conversion of caffeic acid, and no polymerization of 4-vinylcatechol was reported under these conditions [ 13 ]. In the present study, a revised mechanism that does not require any medium for proton transfer and makes the rapid conversion of caffeic acid more plausible is proposed in Figure 4 : Under roasting conditions, caffeic acid 1 performs an intramolecular proton transfer and decarboxylation, yielding 4-vinylcatechol 2 .…”
Section: Resultsmentioning
confidence: 72%
“…Nevertheless, consecutive reactions leading to further enlargement of the conjugated electron system must occur to explain the intense color formation observed in this study. In a recent investigation, it was reported that the electron-donating and -withdrawing groups of 4-hydroxycinnamic acids increase the decarboxylation rate during thermal treatment [ 13 ]. In combination with the data discussed herein, the hypothesis could be formulated that the substitution of the structurally related phenols significantly impacts their color formation under roasting conditions, whereby a higher electron density of the aromatic system correlates with higher extinction coefficients of the resulting reaction products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recently, Yang and coworkers synthesized various functionalized 4-vinylphenols from hydroxycinnamic acids by heating dilute solutions of the acids in N , N -dimethylformamide (DMF), above the boiling point, in sealed reactors. 57 This approach eliminated the need for catalysts or other additives, but may be difficult to scale-up due to the use of low concentrations and elevated pressures.…”
Section: Introductionmentioning
confidence: 99%